COMMUNICATIONS OF CONSENT/DISAGREEMENT IN THE SPEECH OF THE CHARACTERS OF THE NOVEL M.L. STEPNOY "GARDEN" - Yuldasheva Nodira Maxkamovna (Новости образования: исследование в XXI веке, 2023)
The article examines the meaning and features of the communiqués of agreement and disagreement, identifies and analyzes functional and semantic properties, and presents a classification of the communiqués of agreement and disagreement in the novel by M.L. Stepnova.